2021
DOI: 10.1590/1678-4685-gmb-2020-0216
|View full text |Cite
|
Sign up to set email alerts
|

Association between SNP rs527616 in lncRNA AQP4-AS1 and susceptibility to breast cancer in a southern Brazilian population

Abstract: Breast cancer (BC) is the leading cause of death by this disease in women worldwide. Among the factors involved in tumorigenesis, long non-coding RNAs (lncRNAs) and their differential expression have been associated. Differences in gene expression may be triggered by variations in DNA sequence, including single nucleotide polymorphisms (SNPs). In the present study, we analyzed the rs527616 (C>G), located in the lncRNA AQP4-AS1 , using PCR-SSP in 306 BC patients and 312 controls, from a B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In our study, the predictive model was established based on the 9 FRGs-lncRNAs (AQP4-AS1, DANCR, LINC00460, LINC00892, LINC00996, MED4-AS1, SNHG7, UCA1, and WWC2-AS2). Aquaporin 4 antisense RNA 1 (AQP4-AS1) transcribes a lncRNA with unknown function, which was found related to the risk of gastric [31] and breast cancer [32]. We found that AQP4-AS1 act as a protector factor in NSCLC.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, the predictive model was established based on the 9 FRGs-lncRNAs (AQP4-AS1, DANCR, LINC00460, LINC00892, LINC00996, MED4-AS1, SNHG7, UCA1, and WWC2-AS2). Aquaporin 4 antisense RNA 1 (AQP4-AS1) transcribes a lncRNA with unknown function, which was found related to the risk of gastric [31] and breast cancer [32]. We found that AQP4-AS1 act as a protector factor in NSCLC.…”
Section: Discussionmentioning
confidence: 95%
“…Meanwhile, we conducted both internal and external validation to evaluate the accuracy of the signature. Of these prognostic CRlncRNAs, LINC00205 was identified as promoting malignant tumors of LUAD by sponging miR-185-5p ( 45 ); OGFRP1 constitutes an oncogene in NSCLC through the miR-4640-5p/eIF5A axis, and downregulation of OGFRP1 inhibited the progression of NSCLC ( 46 ); MIR31HG could be confirmed as a poor prognostic biomarker and a new therapeutic target for NSCLC patients through activation of the Wnt/β−catenin SP ( 47 ); AQP4-AS1 is downregulated in breast cancer tissues, and its over-expression is related to better prognoses ( 48 ); however, for the first time, LINC00592, TFAP2A-AS1 and CADM3-AS1 were unveiled in lung cancer and could represent new therapeutic targets. The LUAD patients were then classified into low-and high-risk groups according to the median risk score for subsequent analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Energy stress-induced LINC01564 activated the serine synthesis pathway and facilitated hepatocellular carcinogenesis [ 33 ]. AQP4-AS1 plays a potential role in breast cancer [ 34 ]. The lncRNA PIK3CD-AS2 promoted lung adenocarcinoma progression via YBX1-mediated suppression of the p53 pathway [ 35 ].…”
Section: Discussionmentioning
confidence: 99%